Reunion Regional de Cooperación en Mandioca en el Sub-trópico de América Latina (1990, Asuncion, Paraguay). Informe (International Center for Tropical Agriculture, 1990)
A cassava workshop was held in Paraguay to analyze the convenience of improving the communication between professionals working with the crop in Paraguay, Argentina, and southern Brazil, identify specific technical areas of interest to the institutions of each country, and prepare an agenda of future interinstitutional activities to satisfy common information needs. Main points of the reports given by the different participants are summarized. Thematic areas of interest were defined as plant breeding, production, postharvest aspects, and social economics. Regarding plant breeding, the search for tolerance to cold and to bacteriosis was considered prioritary; in the area of production, prioritary areas were handling of planting material, control of bacteriosis, soil management and conservation, and cultural practices. Regarding postharvest aspects, priorities varied according to the country (fresh consumption, starch, wastes, fermentation, feeds, demand surveys, CM, technological diffusion) and in social economics, a need for on-farm research as well as for studies on socioeconomic aspects of production was expressed. (CIAT)